Anxiety of Caught New Type Coronavirus (Covid-19) in Professional Soccer Players - Halil Taşkın; Ramazan Göğebakan; İbrahim Halil Şahin (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate the anxiety of catching a new type of coranavirus (Covid-19) in professional soccer players. soccer players 188 including 42 professional soccer players from the Turkish Super League, 32 players from the TFF 1st League, 41 players from the 2nd League, and 73 players from the 3rd League were voluntarily participated in this study . Average age of the players is 25.04 ± 4.831 years; average height of the players is 180.11 ± 6.246 cm; average body weight of the players is 75.23 ± 6.118 kg,; average sports age of the players is 12.82 ± 4.256 years. In this study evaluating the anxiety of professional soccer players about catching Covid-19, the level of anxiety of soccer players about getting Covid-19 was compared according to the status of being caught and not caught, the leagues they played and their game positions. No significant difference was found in the cases of the soccer players catching or not getting Covid-19. The change between the leagues in which the players play does not make any sense. When the anxiety of catching Covid-19 was examined according to the playing positions, a statistical significance was found in the comparison of the social anxiety scores according to the positions played by the players. In conclusion, while there was no significant relationship between the soccer players catching and not getting Covid-19, and their anxiety about catching Covid-19 for the leagues they played, the anxiety levels of catching Covid-19 were statistically significant to the game positions.